Does suberin accumulation in plant roots contribute to waterlogging tolerance? - Watanabe, Kohtaro; Nishiuchi, Shunsaku; Kulichikhin, Konstantin; Nakazono, Mikio (Frontiers in Plant Science, 2013)
Plants that are adapted to waterlogged conditions develop aerenchyma in roots for ventilation. Some wetland plant species also form an apoplastic barrier at the outer cell layers of roots that reduces radial oxygen loss (ROL) from the aerenchyma and prevents toxic compounds from entering the root. The composition of the apoplastic barrier is not well understood. One potential component is suberin, which accumulates at the hypodermal/exodermal cell layers of the roots under waterlogged soil conditions or in response to other environmental stimuli. However, differences in suberin content and composition between plant species make it difficult to evaluate whether suberin has a role in preventing ROL. In this article, we summarize recent advances in understanding apoplastic barrier formation in roots and, between various plant species, compare the chemical compositions of the apoplastic barriers in relation to their permeability to oxygen. Moreover, the relationship between suberin accumulation and the barrier to ROL is discussed.